Analysis of Changes in Non-Taxable Entrepreneurs to Taxable Entrepreneurs: Case Study on CV ABC - Wibowo, Brigitha Maura Adelia; Juliati; Triatmoko, Hanung; Suranta, Sri (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2024)
This study seeks to gain insights into the company in question by examining the factors involved in confirming its status as a Taxable Entrepreneur (TE), specifically about Value-Added Tax (VAT) and the responsibilities that must be fulfilled by VAT-Registered Persons. Moreover, there are consequences of officially confirming a taxable company for taxpayers officially confirmed by the Director General of Taxes. The author utilized a descriptive qualitative research method to analyze data obtained from CV ABC. The data were processed using interviews and data documentation. The analysis technique included data presentation and conclusion. The results are based on the author's research and analysis, indicating that CV ABC did not immediately confirm its status as a Taxable Entrepreneur independently. The researcher provided a calculation of Taxable Entrepreneur assumptions. CV ABC experienced a decline in sales, leading to losses caused by VAT collection, as the company did not increase selling prices. Due to indications of being confirmed as a Taxable Entrepreneur by authorities, CV ABC must comply with all the consequences and obligations of being a Taxable Entrepreneur as required by the authorities.